PEMBERDAYAAN MASYARAKAT DI KEPENGHULUAN BAGAN BATU BARAT KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Nurman, Muhammad; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aimed to determine the programs and the factors that thread to attending empowerment program in Kepenghuluan Bagan Batu Barat Bagan Sinembah Distric of Rokan Hilir Regency that doing by Community Empowerment (BAPEMAS) Rokan Hilir Regency. This research occurs at the Kepenghuluan Bagan Batu Barat Bagan Sinembah distric Rokan Hilir Regency. This research using qualitative method. The data collection techniques in this study using the technique of in-depth interviews and documentation and the data obtained from the study site will be processed and analyzed further by way of outlining the facts which has been found from the study site.From the interview to the informant and based on the data and information obtained by researchers when doing research on-site research, it can be concluded that the Empowerment program conducted in Kepenghuluan Bagan by Community Empowerment (BAPEMAS) has not been implemented optimally, there are still some obstacles in its implementation, both internally and externally. Inhibiting factors internal include: infrastructure is inadequate, lack of Human Reseources, there is postphone program, lack of coordination, lack of expert people, while factors external lack motivation of the society, officer is inaduquate, lack of Human Resources that Expert, the economic community unoptimal.Keywords: Empowerment, Empowerment Program, Factors on the Program